Information hiding using IDv3 tag in MP3 file (Al-Mansour Journal, 2022)
As we all know that digital information hiding (or steganography) is used to embed data (information) into digital media for the purpose of identification, annotation, and copyright. In other words it is the operation of hiding certain information into a specific cover media such as pictures and audio files or even in a simple text files. In this paper a new approach in hiding information into an MP3 file was proposed, simply instead of using the traditional method of hiding into the actual audio data we will hide our secret messages into the IDv3 tag which is a tag used to store specific information about the MP3 file.The IDv3 tag has gone into a several changes to reach its current version (version 3) containing several interesting features that will be used as a cover for our secret message, first of all a simple overview for the versions and releases of the ID tag is illustrated and display the features of the IDv3 tag which we will use as a cover media.